A dry white season [videorecording (DVD)] - Welland, Colin; Palcy, Euzhan; Sutherland, Donald, 1935-; Sarandon, Susan, 1946-; Brando, Marlon; Suzman, Janet; Prochnow, Jürgen; Mokae, Zakes; Ntshona, Winston; Ntshinga, Thoko; Kani, John; De Keyser, David; et al. (MGM DVD., 2005)
Teacher Ben du Toit sees himself as a caring and just person. When his gardener's son is beaten up by police at a demonstration by black children, he sees that society is built on a foundation of prejudice.